Assessing the Effects of the Transition from Multiple Daily Insulin Injections (MDI) to Continuous Subcutaneous Insulin Infusion in the Intensive Treatment of Type 1 Diabetes Mellitus - Oliveira, SC (2019)
Introduction: Intensive insulin therapy is currently the main treatment in type I diabetes mellitus (DM) which includes multiple daily insulin injections (MDI) and continuous subcutaneous insulin infusion (CSII). The latter has become the preferred therapeutic mode, since it better mimics the physiological pancreatic action, althought there is limited evidence that supports its superiority to MDI. The aim of our study was to assess the effects of the transition from MDI to CSII in the intensive treatment of type 1 DM. Material and Methods: A retrospective longitudinal study was perfonned in MDI patients that transited to CSII between 2006 and 2014. Data were collected regarding to weight, HbA1c, plasma glucose, lipid profile, creatinine, weekly frequency of episodes of hypoglycemia and hyperglycemia and presence of microvascular complications. The effects of the transition to CSII were also compared according to the following subgroups: pre-CSII HbA1c (<= 7.0% vs >7.0%); age (<= 35 years vs > 35 years); gender (male versus female); BMI (<= 25 vs >25 kg/m2); duration of illness (<= 15 years vs > 15 years); total daily dose (TDD) of insulin (<= 45 and > 45 units of insulin); ISF (<= 40 and > 40) and microvascular complications (presence versus absence). Results: The sample included 85 patients, mean age 38 +/- 11 years, 50 (58.8%) female, with duration of the disease 21 +/- 9 years. There was a significant reduction in the frequency of hypo and hyperglycemia events after transition to CSII (3.0 +/- 5.0 vs 2 +/- 2.2 per week, p= 0.001 and 5.5 +/- 6.1 vs 2.5 +/- 2.6 per week, p = 0.05, respectively). We also observed a greater glycemic benefit in the subgroups of patients with poorer metabolic control (HbA1c > 7%) compared to those with HbA1c s <= 7% (Delta HbA1c =-0.55% vs 0.20%, respectively, p < 0.05), for the first 6 months after CSII, being additionally reported a significant increase in HDL-C levels (2.81 +/- 10.34 mg/dL, p = 0.039). Conclusion: In this study, CSII therapy was shown to be more effective compared to MDI in patients with poorer metabolic control, being also noted a significant reduction of weekly frequency of hypo and hyperglycemia events. Notwithstanding the encouraging results linked with CSII, in the future, longer longitudinal studies will be mandatory in order to assess the real relative effectiveness of CSII in the treatment of type 1 DM.